2021
DOI: 10.1002/epi4.12514
|View full text |Cite
|
Sign up to set email alerts
|

Availability, affordability, and quality of essential anti‐seizure medication in Cambodia

Abstract: Objective Epilepsy is a major neurological disorder that requires long‐term medical treatment. Once epilepsy is diagnosed, people with epilepsy face many difficulties in accessing treatment (treatment gap). Our objective was to assess the situation regarding the availability, price, affordability, and quality of anti‐seizure medication (ASM), which are major determinants of access to treatment. Method A cross‐sectional study was performed in provincial/district hospitals and private pharmacies in urban and rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Despite this, the availability of individual medicine was better than availability in many low‐ and middle‐income countries like Zambia, 16 Madagascar, 17 Lao PDR, 18 and India 19 . The availability was similar to the Cambodia study 20 and lower than the Cuba finding 21 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite this, the availability of individual medicine was better than availability in many low‐ and middle‐income countries like Zambia, 16 Madagascar, 17 Lao PDR, 18 and India 19 . The availability was similar to the Cambodia study 20 and lower than the Cuba finding 21 …”
Section: Discussionmentioning
confidence: 93%
“…19 The availability was similar to the Cambodia study 20 and lower than the Cuba finding. 21 The availability of LPG antiseizure medicines was 62.86%, 30%, 55%, and 50% at public, private, Red Cross, and Kenema public pharmacies, respectively. The results showed that antiseizure medicines were more available in the public sector.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed most essential ASMs, except for phenytoin 100 mg in Lao PDR, carbamazepine 200 mg in Lahore, Pakistan, and phenobarbitone 50 and 100 mg in private pharmacies in Cambodia were not affordable. [13][14][15][16][17][18] There was an obvious trend that ASM was more available in public hospitals and limited or unavailable in private sectors or retail pharmacies. [15][16][17] However, the findings from these studies might reflect the tip of the iceberg in the context of the availability and affordability of all ASMs.…”
Section: Key Pointsmentioning
confidence: 99%
“…[13][14][15][16][17][18] There was an obvious trend that ASM was more available in public hospitals and limited or unavailable in private sectors or retail pharmacies. [15][16][17] However, the findings from these studies might reflect the tip of the iceberg in the context of the availability and affordability of all ASMs. As newer ASMs are highly costly, they are not freely available in public hospitals or covered by national health insurance schemes.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation